The Safety and Efficacy of Chemical Pleurodesis Agents in Patients with Malignant Pleural Effusion Admitted in Tertiary Care Hospital - Venkateshwaran Kathamuthu; Rajeshkumar Balakrishnan; Saravanavasan Rajendran; Prabhakaran Rathinam (Journal of Association of Pulmonologist of Tamil Nadu)
Background: Pleurodesis alleviates symptoms such as dyspnea, chest pain, cough and prevents recurrent pleural collections which require repeated thoracentesis. Pleurodesis improves the quality of life as a minimally invasive procedure. Chemical pleurodesis is preferred through tube thoracostomy in limited resource settings. The ideal sclerosing agent should be easily administered, safe, inexpensive, and widely available. The commonly used agents in tertiary care hospitals are talc (10 mg/kg), doxycycline (100 mg/kg), and povidone-iodine (20 mL, 10%). As there was no studies comparing these three together which are widely available in all limited resource settings, this study was conducted to find an efficacious, cost-effective, and safer agent among these three used in patients with malignant pleural effusion. Objectives: The objective of this study was to determine the efficacy and safety of the chemical pleurodesis agents used in patients with malignant pleural effusion. Methods: The study was conducted on 30 patients of malignant pleural effusion admitted to the department of respiratory medicine in the tertiary care hospital. In each of these patients, an intercostal tube of size appropriate to the patient was inserted into the fifth intercostal space along the mid-axillary line. Pleurodesis was performed in order with agents: (1) doxycycline, (2) povidone-iodine, and (3) talc, respectively, if the pleural drain was <150 mL/day and no air leak following the complete expansion of the lung after intercostal drainage. Patients were clinically and radiologically assessed with computed tomography chest on discharge, 1 month, and at the 3rd month for response. Results: Out of 30 patients, 21 patients had complete response (70%). Among those, 9 patients (43%) were treated with talc, 7 patients (33%) were treated with povidone-iodine, and 5 patients were treated with doxycycline (24%). Talc was superior and povidone was nearly efficacious to talc. But doxycycline was inferior at the end of 3 months (P = 0.001). Conclusion: Povidone-iodine had an adequate response nearly equal to the talc which was a highly efficacious pleurodesis agent. Doxycycline had 50% failure and requires repeated pleurodesis for a successful outcome. Most of the adverse events were mild to moderate and were evenly distributed in all groups and could be managed conservatively.